STRIVERS, MAINTAINERS, ACHIEVERS: NETWORKED TRAJECTORIES OF OLDER ADULTS LEARNING TO USE TECHNOLOGY DURING A PANDEMIC - Marler, Will (AoIR Selected Papers of Internet Research, 2021)
While research has explored digital divides in older adults’ technology skills and uses and in their communication uptake during the pandemic, we lack an understanding of the on-the-ground experiences and trajectories of older adults seeking to adopt digital technologies to maintains social connection during the COVID-19 pandemic. What balance of independence and interdependence do older adults seek and experience as they attempt to take up new devices and applications, such as tablets and video chat, during a period of physical distancing? I introduce “strivers,” “achievers,” and “maintainers” to describe different experiences of in(ter)dependence that emerged at the intersection of technology use and physical distancing for participants during and after the technology training program. Independence is reflected among those who were able to translate provided technology resources into an expanded social presence during the pandemic. Interdependence relates to those who became even more dependent on others, with the addition of needed technology support, while aspiring to replace offline relationships with those promised through digital technologies. Simultaneously, by declaring oneself “not lonely despite being alone,” others declared independence despite failing to realize the promise of digital technology as a stand-in for in-person connection. Research on older adults and digital technology can benefit from examining not only the possession of digital skills and support for technology use, but also the meanings that older adults bring to their experiences of inclusion and exclusion as they adapt to digital technologies while aging – and sheltering – in place.